UPAYA GURU BK DALAM MEMINIMALISIR PERILAKU MENYONTEK PESERTA DIDIK DI SMA N 2 RANAH PESISIR KABUPATEN PESISIR SELATAN - Dewi, Ayu Paramita (Bimbingan dan Konseling, 2014)
Based on the phenomenon that researchers have found in the field revealed that the rampant cheating behavior among students in learning both homework, exercises and exams that resulted in students being lazy to study, students generally do not know the impact of cheating behavior, even learners cheating behavior as a habit of thought reasonable in the learning process.This study was classified as descriptive research with quantitative approach. Its population is high school students N 2 Coastal Domains listed in the academic year 2012/2013. The population numbered 586 people. The number of samples are 85 people that as many as 31 people X.3 classes, as many as 28 IX.2 class, class XII.3 25 people and sampling was done by using a random layered (stratified random sampling). The research was conducted by administering the research instruments to students sampled in this study. Collecting data using a questionnaire that revealed cheating behavior of students. The data obtained were analyzed by percentage.The study findings revealed that: (1) Efforts to minimize BK Teacher cheating behavior of students at SMAN 2 Coastal Domains are in very good category of about 12 people, about 11 people fairly category, the category is less about one person, and the categories of both around 61 people or by 71.76%, (2) efforts Master BK meminimalisisr due to the behavior of students cheat at SMAN 2 Coastal Realm is in the category very well about 29 people, about enough category 4 and category both by 61.18% or approximately 52, (3) efforts to minimize contention BK Teacher cheating behavior of students at SMAN 2 Domains Coastal excellent belonging to the category of about 36 people, about enough category 3, and both categories of 54.12%, or about 46 people